1994
DOI: 10.1111/j.1469-8986.1994.tb01028.x
|View full text |Cite
|
Sign up to set email alerts
|

Conscious and nonconscious processes: An ERP index of an anticipatory response in a conditioning paradigm using visually masked stimuli

Abstract: This study investigates the nonconscious elicitation of a previously conditioned response by using a differential conditioning paradigm with visually masked affectively valent facial schematics. Electrodermal (skin conductance response [SCR] and brain (event-related potential [ERP]) activity were main dependent measures. Following a preconditioning phase in which subjects viewed energy masked pleasant and unpleasant facial schematics, conditioning with an aversive shock was established to unmasked presentation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
71
0
2

Year Published

1997
1997
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(81 citation statements)
references
References 58 publications
8
71
0
2
Order By: Relevance
“…When this method is used there is evidence that a CR can be evoked by a CS presented out of awareness if the CS-UCS association was formed in awareness (Öhman, Dimberg, & Esteves, 1988). Wong, Shevrin & Williams (1994) replicated this finding and discovered brain responses to subthreshold presentations of the CS. Esteves, Dimberg and Öhman (1994a) found that CRs to angry face CS+s survived backward masking but CRs to happy face CS+s did not (see also Esteves, Parra, Dimberg & Öhman, 1994b).…”
Section: Autonomic Conditioning Outside Of Awarenesssupporting
confidence: 68%
“…When this method is used there is evidence that a CR can be evoked by a CS presented out of awareness if the CS-UCS association was formed in awareness (Öhman, Dimberg, & Esteves, 1988). Wong, Shevrin & Williams (1994) replicated this finding and discovered brain responses to subthreshold presentations of the CS. Esteves, Dimberg and Öhman (1994a) found that CRs to angry face CS+s survived backward masking but CRs to happy face CS+s did not (see also Esteves, Parra, Dimberg & Öhman, 1994b).…”
Section: Autonomic Conditioning Outside Of Awarenesssupporting
confidence: 68%
“…Thus, a conditioned stimulus can elicit affect, as assessed electrophysiologically, even when presented outside of awareness. Numerous other studies have produced similar results (see J. Weinberger, in press ;Wong, Shevrin, & Williams, 1994 ) with dependent variables ranging from skin conductance to facial electromyography (EMG, which measures facial muscle indicators of emotion) to evoked-related brain potentials (ERPs). Other studies show that classically conditioned emotional responses can be not only elicited but acquired without consciousness (e.g., Bunce, Bernat, Wong, & Shevrin, 1995 ;Esteves, Dimberg, & Ohman, 1994 ).…”
supporting
confidence: 50%
“…There is much evidence that facial expressions can be detected pre-consciously and can influence psychophysiological and behavioural responses without awareness of the particular expression (e.g., Dimberg & Ohman, 1996;Dimberg, Thunberg, & Elmehed, 2000;Johnsen & Hugdahl, 1991Mogg & Bradley, 1999;Murphy & Zajonc, 1993;Niedenthal, 1990;Ohman, Esteves, & Soares, 1995;Robinson, 1998;Saban & Hugdahl, 1999;Whalen et al, 1998;Wong, Shevrin, & Williams, 1994). All of these studies presented masked faces for very brief exposure duration (target-to-mask stimulus onset asynchrony [SOA] of less than 35 ms).…”
Section: Introductionmentioning
confidence: 99%